(untitled) (Comprehensive Journal of Science, 2025)
Engineering workshops present complex occupational health and safety (OHS) challenges due to powered equipment, hot work activities, hazardous maintenance tasks, and diverse user groups. In Libya, empirical evidence on workshop-level safety readiness within technical institutes remains limited. This paper reports a case study of OHS practices and control implementation at the Target Institute using a structured 44-item questionnaire. A cross-sectional survey design was adopted, and seventy respondents provided usable data (N = 70). The instrument covered six domains relevant to engineering workshop operations: machine and equipment safeguarding, hazardous energy control, hot work and chemicals, noise/vibration/ergonomics, risk assessment and permit-to-work, and safety culture/training/PPE. Statistical analyses included descriptive statistics, Relative Importance Index (RII), reliability testing (Cronbach’s α), normality tests, ANOVA and Welch ANOVA with effect sizes, correlation analysis, and exploratory regression. The overall scale demonstrated high reliability (α = 0.947). Results indicate moderate OHS readiness, with notable deficiencies in noise, vibration, and ergonomic controls and in formalized risk assessment and permit-to-work execution. Significant differences were observed across respondent roles and exposure frequency.